Hloma Mathonsi, the Zulu blacksmith: a record by the Reverend H. F. O. Dedekind in 1929 - Maggs, T. (Southern African Humanities, 2021)
The missionary Rev. H. F. O. Dedekind visited and photographed a Zulu smith in 1929 in the Mzinyathi (Buffalo) River valley of Natal. The account of this visit contains information of both historical and ethnographic interest, including some unique observations on local smithing. To cite this article: Maggs, T. 1986. Hloma Mathonsi, the Zulu blacksmith: a record by the Reverend H. F. O. Dedekind in 1929. Annals of the Natal Museum27 (2): 481-9.